Effect of Menstruation Cycle on Mood, Affection, Mental Health and Valence - Dr. Sunil Kumar Mishra (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2023)
There is a quote from Elizabeth Gilbert’s Eat, Pray, Love; “You are, after all, what you think. Your emotions are the slaves to your thoughts, and you are the slave to your emotions.” Expanding our personal boundaries and breaking gender stereotypes can surely enable us to be examples of positivity and confidence. The women of the present generation have generally received higher education than the women of their preceding generation. There have been far reaching consequences in the economic status of their families. Self-esteem refers to how you feel about yourself overall; how much esteem, positive regard or self-love you have. It’s not a quality that changes very much since it is related to a broad sense of personal value or self worth. People with high self-esteem tend to see the universe as a pretty friendly place. Self esteem adversely affects physical and mental health. The clinical literature suggests that low self esteem is associated with depression, hopelessness, and suicidal tendencies which can further lead to attempt of suicide. Keywords: Higher Education, Mental Health, Menstruation